A Study Of The Inventory Models With Supply Chain Management: A Research Review (Journal of Namibian Studies : History Politics Culture, 2023)
The proliferation of industrial engineering fields and manufacturing sectors has expedited the implementation of mathematical methods for inventory analysis. A supply chain encompasses all entities that participate in the direct or indirect satisfaction of a customer's demand, such as suppliers, manufacturers, transporters, warehouses, and carriers. Inventory management is of the utmost importance in the supply chain due to its direct impact on service and cost. Due to the unpredictability of supply and demand, inventory must be managed at specific points along the supply chain to guarantee adequate service. Elevations to inventory policies have the potential to profoundly affect the effectiveness and agility of the supply chain. Administrators are tasked with the responsibility of identifying primary inventory categories and devising the corresponding dimensionaling method. An organization may designate cycle inventory, safety inventory, and seasonal inventory, and a set of indicators may be utilized to furnish a comprehensive synopsis of the inventory. In the past two decades, supply chain management (SCM) has garnered considerable attention from both the academic and industrial sectors. Supply chain management (SCM) endeavors to decrease inventory levels, enhance revenue generation via streamlined consumer demand fulfillment, and expedite transaction processing via real-time data exchange. It is a frequent occurrence in the manufacturing industry for substandard product quality to result from the capabilities of the manufacturing process. There are consumers who have a preference for purchasing items that are imperfect or flawed, but are available at a discounted price. A restricted quantity of faulty products are considered acceptable for purchase at a discounted rate, whereas the remaining items exhibiting the most severe flaws are completely rejected. In order to uphold a superior level of quality and exhibit consideration for customers, any remaining defective items are excluded from the sale.